The siri' value in Bugis tribe family parenting - Marhani, Marhani; Prihartanti, Nanik; Purwandari, Eny (Universitas Muhammadiyah Surakarta, 2021)
Abstract. Parents embed values that they value from one generation to the next through nurturing. The purpose of this study is to describe the childcare in the Bugis family. The study used a qualitative approach with case study methods. Data collection uses semi-structured interviews with thematic analysis. The informant was chosen in purposive sampling which took three units of the Bugis family consisting of fathers, mothers, and 15-year-old children and indigenous people as supporting informant. The results of this study show that in the three families of Bugis tribe prioritizes siri' value especially in the parenting of daughters. In families who nurture boy, in addition to instilling a siri' value also imparts the value of ammaccang and reso'. The process of planting those values, parents have full authority on the children in applying the rules and give understanding to the child, as well as values in the family can be practiced and maintained. If the child commits a value violation, then the parent is given punishment and provides explanation to the child regarding the parent's actions, so that the child can accept and behave in accordance with the expectations desired parents.Keywords: family; Siri’ value; child parenting; Bugis tribe